Regulation of Fixed Income Securities Markets in the United States - Friedman, Felice B. (World Bank, Washington, D.C., 2013)
The author looks at the development and regulation of the fixed income securities market in the United States. The U.S. fixed income market is one of the oldest and most developed debt markets in the world. It is also one of the most heterogeneous, with the four key market segments-government securities, the securities of government-sponsored enterprises, municipal securities, and corporate debt securities-all being relatively large and deep. The author describes the evolution of fixed income market regulation in the United States, discussing both primary and secondary market regulation. She also looks at market integrity issues and the enforcement authority of the U.S. Securities and Exchange Commission, which is broad and has played an important role in the effectiveness of regulation. The author concludes that the fact that the U.S. fixed income market flourished for many years in the absence of regulation must be seen in a broader legal and regulatory context. While the debt market itself may have been unregulated, it operated within a larger framework of equity market regulation and enforcement, complemented by a long history of bank supervision that had a significant impact on its development. It is this context that permitted U.S. authorities to adopt regulation in stages, in response to differing demands and priorities. The dynamic nature of the regulation of the U.S. fixed income market-its development in response to market crises-underscores the need for regulation to remain responsive to market developments, and to be adapted to domestic constraints.